Developing complex analysis textbook to enhance students’ critical thinking - Setyawan, Fariz; Prasetyo, Puguh Wahyu; Nurnugroho, Burhanudin Arif (JRAMathEdu (Journal of Research and Advances in Mathematics Education), 2020)
Critical thinking skill was needed since problems in daily life required a solution. To solve the problems, the students collect the data as a consideration in making the right decision. Moreover, the students also need good critical thinking skills. To develop a good critical thinking skill, the researcher develops a textbook of Complex Analysis and Application, especially in complex numbers. In this research, a qualitative investigation was carried out in the development of the textbook. This textbook supports the mathematics education students of Universitas Ahmad Dahlan in learning complex analysis course. Researchers did a walkthrough to the expert in assessing the content and construct to validate the textbook. The development model used by researchers is a 4 D model. A 4-D model used in this study is consists of defining, designing, developing, and disseminating. In defining, the researcher adequate materials related to the complex numbers such as the rational number and real number and its properties in addition and multiplication. In designing, some explanation in the textbook is followed by Why and How questions. Open questions are used to stimulate the students’ critical thinking. Based on the walkthrough result, some notation in the textbook, especially mathematics symbols, must be revised using a proper mathematics equation. In addition, some concept should be clearly defined such as z‐¹ = 1/z where the value of z ≠ 0. As a result of the validity construct, the explanation given in the textbook used a step-by step exercise. In disseminating, the students can easily access the textbook and answer the questions using their reasoning. The textbook is valid and readable.